Dentists' lived experience of providing dental care during the COVID-19 pandemic: A qualitative study in Mashhad, Iran - Hoseinzadeh, Melika; Sa’adAbadi, Zahra; Maleki Kambakhsh, Sara; Babazadeh, Saber (Frontiers in Oral Health, 2023)
Background: This study was aimed to explore the lived experiences of dentists practicing in Mashhad, Iran, during the COVID-19 pandemic and identify possible influencing factors for providing dental health in this era. Methods: Sixteen dentists took part in this qualitative phenomenological study. Semi-structured face-to-face interviews were performed and evaluated using a qualitative content analysis approach. The MAXQDA program (2020) was used to code and classify the data. Purposive sampling, audio recording, member checking, and peer review were employed to verify transferability, reliability, and validity. The interview transcripts were transcribed, and sentences and remarks relevant to the study's goal were retrieved and classified. Results: Six hundred twenty-eight codes were extracted after several readings of the texts. Five core themes and fourteen sub-themes were determined after deleting repeated themes and axial coding. The main five themes included: "Coping with the COVID-19 pandemic," "Alternations in providing dental care," "Infection control," "COVID-19-related news and information sources," and " Positive and negative aspects of COVID-19 in dental care Pros and cons of COVID-19 in dental care". Conclusions: During the COVID-19 epidemic, dentists noted various challenges in delivering routine dental treatment, including a lack of resources, reliable and clear straightforward guidelines for dentists, and governmental policies for dental facility restrictions. Dentists concluded that governmental financial, educational, and financial support from the government would greatly significantly enhance the delivery of community dental care services. With the right strategies and lessons learned, dentists may be better prepared for future challenges in global health care.